Paleontology and geology of Laetoli: human evolution in context Volume 2: fossil hominins and the associated fauna - Harrison, Terry (Vertebrate Paleobiology and Paleoanthropology., 2011)
This volume 2 and its companion volume 1 present the results of new investigations into the geology, paleontology and paleoecology of the early hominin site of Laetoli in northern Tanzania. The site is one of the most important paleontological and paleoanthropological sites in Africa, worldrenowned for the discovery of fossils of the early hominin Australopithecus afarensis, as well as remarkable trails of its footprints. The first volume provides new evidence on the geology, geochronology, ecology, ecomorphology and taphonomy of the site. The second volume describes newly discovered fossil hominins from Laetoli, belonging to Australopithecus afarensis and Paranthropus aethiopicus, and presents detailed information on the systematics and paleobiology of the diverse associated fauna. Together, these contributions provide one of the most comprehensive accounts of a fossil hominin site, and they offer important new insights into the early stages of human evolution and its context.